(untitled) (Journal of Laboratory Animal Science, 2018)
Laboratory animals have contributed greatly in understanding human physiology and pathology. However, differences in biology do not allow us to definitively interpret the results of experiments in animals. Transplanting human cells and tissues into mice has therefore been one of the milestones in humanizing laboratory animals. However, this necessitates complete replacement of the mouse system by the human system, the most explored of which is the immune system. But this has not been easy as each phenotypic deletion in mice has unraveled the complexity of host (mouse) defense mechanisms and at the same time shed more light on the development of the human immune system. Because humanized immune mice lack the armory to reject xenotransplants, they are being extensively used to implant and study other human systems, including infectious diseases. This review summarizes the history of humanizing the mouse, the technical advancements, the knowledge gained in the process, their use as well as the outlook in this fascinating and rapidly advancing field.